THE COST OBTAINED BY APPLYING PRECEDENCE DIAGRAM METHOD TOWARD THE TIME OPTIMIZATION ON BUILDING DEVELOPMENT PROJECTS - I Made Tapa Yasa; I Made Anom Santiana; I Gede Sastra Wibawa; I Wayan Suasira (Logic : Jurnal Rancang Bangun dan Teknologi, 2018)
The complexity of the project expands along with the progress of human civilization. The problems that appear will be more numerous and complicated. The role of project management is indispensable in order to address and prevent these problems, so that the cost,the quality and the time agreed upon can be realized. Cost and time relationship is not directly proportional, so it is necessary to determine the optimal time by optimum cost. Optimization is a best effort undertaken by planning various alternative methods of implementation, in order to obtain optimal timing of projects with optimum cost. Planning and scheduling are the backbone of the entire project, which is based on clear objectives. Microsoft Project as one of the scheduling software based on Precedence Diagram Method (PDM) provides many advantages, one of which scheduling can be done more quickly and thoroughly.In this research, it is created six alternative models as follows: In the first alternative ,it is acquired the project period of 256 days , at a cost of Rp2,190,234,913.43 ; In the second alternative , the was obtained the project period of 150 days , with a cost of Rp1,903,674,873.6 ; In the third alternative , it was obtained the project period of 102 days , at a cost of Rp1,873,215,897.61 ; In the alternative IV , it was obtained the project period of 99 days , at a cost of Rp1,895,159,526.12 ; In the alternative V , the project period was 96 days , at a cost of Rp2,019,623,191.13 ; In alternate VI , the project period was 89 days at a cost of Rp2,090,543,033.77. From the above calculation, then the result is interpolated in order to obtain the optimum time for the development project. The optimum time obtained is 120 calendar days, at a cost of Rp. 1,884,638,013.61.